A View of Historical Philosophy from the Perspective of Tan Malaka - Yuwono, Ardi Tri (Abjad Journal of Humanities & Education, 2025)
The philosophy of history has a crucial role to play in understanding not only "what happened," but also "why and where" the direction of historical development. One of the figures who made significant contributions to the thought of historical philosophy in Indonesia was Tan Malaka. Tan Malaka presents a perspective on historical dynamics based on historical materialism, class struggle, and socialist vision. This research aims to analyses Tan Malaka's historical philosophical views systematically, especially related to the concept of direction of historical movement, the actors involved, and the purpose of the direction of the movement of history. The research method used in this study is a historical method with a qualitative approach, utilizing historical sources, such as Madilog, Naar de Republiek Indonesia, Aksi Massa, and others. Tan Malaka developed a philosophy of history based on dialectical materialism adapted to the conditions of the colonized society, emphasizing the importance of class conflicts, the power of the masses, and revolution as the main drivers of history. The concept of "100% independence" is at the core of his thinking which demands comprehensive political, economic, and cultural independence. His analysis of the internal contradictions of colonialism, the role of the inferior priayi, and the criticism of the incomplete revolution provides a critical perspective in understanding the history of Indonesia and contemporary issues that must be faced.